Urbanization and Growth : Commission on Growth and Development - Spence, Michael; Annez, Patricia Clarke; Buckley, Robert M. (World Bank, 2012)
Structural change is a key driver of rapid growth: countries diversify into new industries, firms learn new things, people move to new locations. Anything that slows this structural change is also likely to slow growth. Because urbanization is one of the most important enabling parallel processes in rapid growth, making it work well is critical. Urbanization's contribution to growth comes from two sources: the difference between rural and urban productivity levels and more rapid productivity change in cities. In the early decades of development, when the majority of the population is still rural, the jump from rural to urban employment makes a big contribution to growth. As cities grow larger, the second effect faster gains in urban productivity - begins to dominate, as it operates on a larger base. Mortgages can improve households' ability to buy decent housing. But finance relaxes demand constraints only. Unless it is accompanied by measures to increase supply, better finance may result in overshooting prices. This volatility can jeopardize macroeconomic stability. In a typical pattern, strong income growth leads to a rapid increase in housing demand. An injection of liquidity from some source, often overseas, may help over stimulate the market, leading to over optimism and a dangerous concentration of wealth in real estate.